2021
DOI: 10.1186/s42523-021-00109-0
|View full text |Cite
|
Sign up to set email alerts
|

Captivity reduces diversity and shifts composition of the Brown Kiwi microbiome

Abstract: Background Captive rearing is often critical for animals that are vulnerable to extinction in the wild. However, few studies have investigated the extent to which captivity impacts hosts and their gut microbiota, despite mounting evidence indicating that host health is affected by gut microbes. We assessed the influence of captivity on the gut microbiome of the Brown Kiwi (Apteryx mantelli), a flightless bird endemic to New Zealand. We collected wild (n = 68) and captive (n = 38) kiwi feces at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 37 publications
8
40
0
Order By: Relevance
“…Similarly, captive birds tend to have distinct gut microbiota from their wild counterparts (San Juan et al 2021). These studies support a strong role of the environment, including diet, in shaping the avian gut microbiome.…”
Section: Introductionsupporting
confidence: 54%
“…Similarly, captive birds tend to have distinct gut microbiota from their wild counterparts (San Juan et al 2021). These studies support a strong role of the environment, including diet, in shaping the avian gut microbiome.…”
Section: Introductionsupporting
confidence: 54%
“…Host environment had nearly an overall significant effect on the Callithrix gut microbiome diversity. Significant differences were found between all host environmental classes for marmoset gut microbiome beta diversity, which is a result observed in various other animals (e.g., kiwis 15 , Tasmanian devil 17 , mice 16 , primates 5 , raptors 69 , rhinos 18 , woodrats 70 ). A unique aspect of our study was the inclusion of hosts translocated from the wild into captivity, which were also significantly different from wild and captive hosts in terms of gut microbiome alpha diversity.…”
Section: /19mentioning
confidence: 53%
“…More closely related hosts seem to share more similar microbiome communities than more distantly related hosts (i.e., phylosymbiosis) 6,7 , and gut microbiome communities are usually enriched for bacteria associated with the main macronutrients of a host's feeding strategy [8][9][10][11][12] . Yet, environmental factors significantly alter individual host microbiomes 10,12 , as evidenced by differences in microbiome composition between wild and captive conspecifics across a variety of animal taxa [13][14][15][16][17][18][19] . Gut microbiome studies of captive and wild mammals show that non-human primates (NHPs) experience relatively large losses of native gut microbiome diversity in captivity compared to the wild 5,13 .…”
Section: Introductionmentioning
confidence: 99%
“…While many wild animals are reared in captivity for reasons spanning scientific research, to education, leisure and conservation, there is growing evidence that conditions in captivity alter the microbial community associated with animals. Some studies reported that the microbial diversity dropped in captivity 5 10 , probably due to the simplification of the environment in which hosts live. However, evidence supporting the opposite pattern has also been reported in some other species 8 , 11 , although it has been suggested these observations might be spurious 12 .…”
Section: Introductionmentioning
confidence: 99%